Rethinking Depictive Secondary Predicates. A Pair- Merge approach and the Adjunct Condition - Demonte, Violeta (Linguística: Revista de Estudos Linguísticos da Universidade do Porto, 2021)
In this article I will propose a new analysis of depictive secondary predication structures. Previous studies of these structures are framed within different approaches: C-command / categorial approaches (Williams 1980, Rothstein 1983, 2001, Demonte 1988, Mallén 1991, Bowers 1993, among others), C-command and Multiple Agree approaches (McNulty 1988, Irimia 2012), linearization after ‘Lateral Movement’ and attachment of identical eventive heads (Gallar 2017), or Parallel-Merge approaches (Irimia 2012, You 2016). Following Chomsky (2019) and Bošković (2020), among others, I will claim here, first, that adjunct depictive secondary predicates start as members of a Pair-MERGE(d) conjunction/ adjunction structure which is unlabeled. There are as many members of these pair merged phrases as modifiers in a sentence, and they are unbounded and unstructured. Pair merged structures are in principle opaque and non-sensible to syntactic operations. However, since they are semantically and syntactically conjoined phrases they have each a Link element. This Link merges at the edge of the phase at which the modifier is conjoined thus allowing extraction out of the opaque domain. I will suggest that perhaps Tagalog expresses overtly these links. I will previously present a detailed description of the properties of DPS in Spanish.